2020
DOI: 10.3390/nu12061601
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Polyunsaturated Fatty Acids Inhibit the Function of Human URAT1, a Renal Urate Re-Absorber

Abstract: The beneficial effects of fatty acids (FAs) on human health have attracted widespread interest. However, little is known about the impact of FAs on the handling of urate, the end-product of human purine metabolism, in the body. Increased serum urate levels occur in hyperuricemia, a disease that can lead to gout. In humans, urate filtered by the glomerulus of the kidney is majorly re-absorbed from primary urine into the blood via the urate transporter 1 (URAT1)-mediated pathway. URAT1 inhibition, thus, contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 33 publications
(55 reference statements)
0
19
0
1
Order By: Relevance
“…It is well established that fatty acids (FAs) influence a range of metabolic and inflammatory diseases [ 53 , 54 ] and cancer [ 55 ]. A recent study demonstrated the relationship between FAs and hyperuricemia: of 25 FAs tested in vitro [ 56 ], nine unsaturated FAs exhibited URAT1 inhibitory effects at 100 μ M, but no saturated FAs showed any effects. In particular, three long-chain unsaturated FAs exhibited strong URAT1 inhibitory effects: eicosapentaenoic acid (EPA) (compound 17) ( Figure 4 ), α -linolenic acid (ALA) (compound 18) ( Figure 4 ), and docosahexaenoic acid (DHA) (compound 19) ( Figure 4 ), which had IC 50 values of 6.0, 14.2, and 15.2 μ M, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that fatty acids (FAs) influence a range of metabolic and inflammatory diseases [ 53 , 54 ] and cancer [ 55 ]. A recent study demonstrated the relationship between FAs and hyperuricemia: of 25 FAs tested in vitro [ 56 ], nine unsaturated FAs exhibited URAT1 inhibitory effects at 100 μ M, but no saturated FAs showed any effects. In particular, three long-chain unsaturated FAs exhibited strong URAT1 inhibitory effects: eicosapentaenoic acid (EPA) (compound 17) ( Figure 4 ), α -linolenic acid (ALA) (compound 18) ( Figure 4 ), and docosahexaenoic acid (DHA) (compound 19) ( Figure 4 ), which had IC 50 values of 6.0, 14.2, and 15.2 μ M, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In this model, the URAT1-expressing plasmid is transiently transfected into cells for 1-2 day protein expression, and the cells are then assayed for [ 14 C] uric acid uptake at certain time points (20 s, 5 min, 10 min) [ 21 , 76 ]. For example, for the inhibition of URAT1 by fatty acids, only 20 s of incubation is needed for uric acid uptake, which helps exclude the impact of fatty acids on the plasma membrane [ 56 ]. This method is easy, convenient, and quick.…”
Section: Resultsmentioning
confidence: 99%
“…A study reported that consumption of fish containing omega-3 PUFA was associated with a lower propensity of recurrent gout flares. [35,36] The exact mechanism is elucidated to be as follows: inhibition of caspase-1 activation, IL-1β secretion, inhibition of NLRP3 inflammasome activation and chemotaxis. [37] Other therapies which show promise in treating gout, but require further research include guava leaves, red ginger and cocoa.…”
Section: Teamentioning
confidence: 99%
“…Human embryonic kidney 293 (HEK293)-derived 293A cells were maintained in Dulbecco's Modified Eagle's Medium (Nacalai Tesque, Kyoto, Japan) supplemented with 10% fetal bovine serum (Biowest, Nuaillé, France), 1% penicillin-streptomycin (Nacalai Tesque), 2 mM L-glutamine (Nacalai Tesque), and 1 × non-essential amino acid (Life Technologies, Tokyo, Japan) at 37 • C in a humidified atmosphere of 5% CO 2 in air (v/v), following our previous study [11]. To obtain ABCC11-expressing 293A cells for the plasma membrane vesicles, we performed plasmid transfection using polyethylenimine MAX (1 mg/mL in Milli-Q water, pH 7.0; Polysciences, Warrington, PA, USA) [12] or adenovirus infection [9], as described previously.…”
Section: Cell Culturementioning
confidence: 99%